EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SMA NEGERI 1 BATANG NATAL - Adelina Nasution; Eva Yanti Siregar; Hanifah Nur Nasution (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
Abstract This study aims to find out the real picture of 1 The Effectiveness of the Implementation of Team Assisted Individualization Type Cooperative Learning on Mathematical Problem Solving Ability of SMA Negeri 1 Batang Natal Students. The research method is an experimental method through pre-test and post-test which provides a significant picture of whether there is effectiveness of the Team Assisted Individualization (TAI) type cooperative learning model on students' mathematical problem solving abilities. The research population was all students of class X SMA Negeri 1 Batang Natal. The research sample was class X IIS-2 which opened 21 people. The instruments are lesson plans, observation sheets and tests. Then descriptive data analysis is about the state of the second variable, namely the launch of the TAI learning model (variable X) to improve students' problem solving skills (variable Y) in class X SMA Negeri I Batang Natal. Then to find out whether there is an influence between the second variable, the t-test formula is used. From the results of data analysis, it is known that the average value before applying the Team Assisted Individualization (TAI) model, the average value is 58 categories